Synthetic peptides derived from ribosomal proteins of leishmania spp. in mucocutaneous leishmaniasis: Diagnostic usefulness (2017)
Background: The serological diagnostic methods currently available for mucocutaneous leishmaniasis (MCL) lack specificity when complete parasites are used; however, such specificity increases when protein fractions are used. Ribosomal proteins have been reported to induce antibodies in animal and humans infected with the parasite, making them a worth candidate to assess its diagnosis potential. Objective: This study was thus aimed at evaluating synthetic peptides derived from Leishmania braziliensis ribosomal proteins S25 and S5 as antigen candidates for diagnosing MCL by ELISA Methods: It was used 8 and 13 peptides derived from ribosomal proteins 25 and S5 respectively as antigens in order to detect IgG antibodies by ELISA in people with active MCL, Chagas disease (CH) and autoimmune disease (AID). Results: 4 of these 21 peptides (P4, P6, P19 and P21) had the greatest sensitivity (21.7%, 13.04%, 20% and 20%, respectively) as well as having 95%, 100%, 100% and 82.5% specificity, respectively. Conclusion: The study revealed the limited usefulness of the peptides being studied as a diagnostic tool in the conditions used here, because its low sensitivity, but it is worth highlighting that the use of peptides as antigen in the serodiagnosis of MCL may overcome the cross reaction presented with other antigens, thus avoiding false positives.